A taxonomy of digital intensive sectors - Calvino, Flavio; Criscuolo, Chiara; Squicciarini, Mariagrazia (Paris, 2018)
"This study proposes a taxonomy of sectors according to the extent to which they have gone digital. The taxonomy accounts for some of the key facets of the digital transformation, and recognises that sectors differ in their development and adoption of the most advanced “digital” technologies, in the human capital needed to embed them in production and in the extent to which digital tools are used to deal with clients and suppliers. The indicators used to classify 36 ISIC revision 4 sectors over the period 2001-15 are: share of ICT tangible and intangible (i.e. software) investment; share of purchases of intermediate ICT goods and services; stock of robots per hundreds of employees; share of ICT specialists in total employment; and the share of turnover from online sales. The study further proposes an overall summary indicator of the digital transformation in sectors which encompasses all the considered dimensions."